Aerodynamic behavior of a compound wing configuration in ground effect - Jamei, Saeed; Maimun, Adi; Mansor, Shuhaimi; Priyanto, Agoes; Nor Azwadi, Nor Azwadi; Tofa, M. Mobassher (Penerbit UTM Press, 2014)

(untitled)
The aerodynamic coefficients of wing in ground effect can be affected with its design which can be the main parameter for efficiency of wing-in-ground effect craft. In this study, the aerodynamic coefficients of a compound wing were numerically determined in ground effect. The compound wing was divided into three parts with one rectangular wing in the middle and two reverse taper wings with an anhedral angle at the sides. An NACA6409 airfoil was employed as a section of wings. Three dimensional (3D) computational fluid dynamics (CFD) was applied as a numerical scheme. A realizable k-e turbulent model was used for simulation the turbulent flow around the wing surfaces. For validation purpose, the numerical results of a compound wing with aspect ratio 1.25, at ground clearance of 0.15 and different angles of attack were compared with the current experimental data. Then, the aerodynamic coefficients of the compound wings were computed at various ground clearances and angle of attack of 4°. According to pressure and velocity distribution of air around wing surfaces, ground clearance had considerable effects on ram effect pressure and tip vortex of the compound wing, and aerodynamic coefficients of the compound wing had some improvements as compared with the rectangular wing.